Floristic composition and diversity of mangroves in selected sites in the province of Antique, Panay Island, Philippines. - Balinas, Lucelle V.
The study covers the floristic composition of true mangrove species and the mangroves's diversity on selected sites in the province of Antique during the time of sampling only